2002
DOI: 10.1007/s00018-002-8431-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis sporulation and stationary phase gene expression

Abstract: Bacillus subtilis cells entering stationary phase due to nutrient deprivation have a number of options. Complex interconnected regulatory circuits govern differential gene expression patterns that channel the cell along the path it has sensed is most advantageous for survival in the environment. The actual choice depends upon the activity of an elaborate signal transduction network (the phosphorelay) that ultimately affects the activity of two key transcription factors, SpoOA and AbrB. Should the cell commit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
171
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 81 publications
3
171
2
2
Order By: Relevance
“…AbrB is a transitionstate regulator that represses transcription of several B. subtilis genes during exponential phase and is inactive under conditions of nutrient limitation and high cell density (reviewed in ref. 46). We found that transcription of rapI, measured with a rapI-lacZ promoter fusion, increased Ϸ5-fold in an abrB mutant (CAL26), relative to wild-type cells (CAL15), indicating that AbrB represses rapI transcription, either directly or indirectly.…”
Section: Regulation Of Icebs1 Excision and Transfer By Intercellular mentioning
confidence: 82%
“…AbrB is a transitionstate regulator that represses transcription of several B. subtilis genes during exponential phase and is inactive under conditions of nutrient limitation and high cell density (reviewed in ref. 46). We found that transcription of rapI, measured with a rapI-lacZ promoter fusion, increased Ϸ5-fold in an abrB mutant (CAL26), relative to wild-type cells (CAL15), indicating that AbrB represses rapI transcription, either directly or indirectly.…”
Section: Regulation Of Icebs1 Excision and Transfer By Intercellular mentioning
confidence: 82%
“…Each cell type receives a copy of the bacterial chromosome, and deploys specific but interdependent genetic programmes controlled by the successive appearance of the s F , s E , s G and s K subunits of RNA polymerase (reviewed by Errington, 2003;Hilbert & Piggot, 2004;Stragier & Losick, 1996). Entry into sporulation is induced by nutrient starvation, and is mainly controlled through phosphorylation of the Spo0A response regulator (Burbulys et al, 1991;Phillips & Strauch, 2002;Sonenshein, 2000). Spo0A~P controls the expression of a large regulon which includes the genes encoding the first compartment-specific regulators s F and s E , as well as genes required for the asymmetric partitioning of the cell (Errington, 2003;Hilbert & Piggot, 2004;Stragier & Losick, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Other genes, such as those for spore formation, have weak binding sites and are only activated when 0A∼P accumulates to high levels (5, 7). The accumulation of 0A∼P is governed by a regulatory network built around a four-component cascade in which the relay protein Spo0F (0F) is phosphorylated by KinA and other kinases (6,8). 0F∼P, in turn, transfers the phosphate to Spo0B (0B), which transfers the phosphate to 0A (Fig.…”
mentioning
confidence: 99%
“…Finally, the fourth pathway (0A∼P┤ abrB┤ spo0E) is a negative feedback loop in that 0E drains phosphates from the relay (for review see ref. 8).…”
mentioning
confidence: 99%